Production of a methyl ester from the microalgae Nannochloropsis grown in raceways on the French west coast. (1st August 2015) - Perrier, Béatrice; Crampon, Christelle; Guézet, Olivier; Simon, Coralie; Maire, François; Lépine, Olivier; Pruvost, Jérémy; Lozano, Paul; Bernard, Olivier; Badens, Elisabeth
Graphical abstract: Highlights: Microalgae appeared to be highly sensitive to climatic conditions. With the high level of free fatty acids in lipids transesterification was complex. Poor oxidation stability in the final fuel was detrimental to engine injectors. Storage must be controlled to avoid the degradation of biomass over time. This energy intensive pathway could benefit from the use of renewable electricity. Abstract: The present article describes the production of oil from autotrophic microalgae grown in raceways in France, and presents the bench test results of a Diesel monocylinder engine with the derived biodiesel (methyl ester). The cultivation of Nannochloropsis has been performed under nitrogen limitation in order to increase the lipid content of the microalgae. After harvesting, a drying operation has been carried out so as to obtain a dry microalgae powder with controlled water content. Neutral lipids were then recovered using supercritical carbon dioxide extraction technology applied to the dry powder. One hundred kilograms of dry microalgae has been treated leading to about five kilograms of algal oil, free of polar lipids, that has been transesterified with methanol. The fuel obtained has been blended with a standard biofuel-free Diesel fuel (10% algal fuel/90% standard Diesel fuel B0) and engine tests have been carried out with the resulting blend (B10). In order to compare with well-known fuels similar engine tests were performed with B0 and with a B10 fuel made of ten percent vegetable oil methyl ester complying with the European 14214 fuel standard (B10 EU-type). The B10 quality was rather close to Diesel fuel except for oxidation stability, which was well below the minimum limit for Diesel fuel. The behavior of the B10 fuel appears to be very similar in terms of combustion efficiency and pollutant emissions to the one of the standard Diesel fuel B0.